Europol: Internet Organised Crime Threat Assessment (IOCTA) 2021. Issue 12 (December 2021) - Unknown
Abstract : The annual Internet Organised Crime Threat Assessment (IOCTA) report has typically seen cybercrime as an area in which steady evolution is the norm. There are fads and phases, to be sure, but rarely sudden change.